2009
DOI: 10.1542/peds.2009-0233
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Accessibility to Providers and Vaccination Compliance Among Children With Medicaid

Abstract: Within our low-income, urban population, children with higher spatial accessibility to pediatric vaccination providers were more likely to be up-to-date with vaccinations. This association may guide future studies and efforts to ensure adequate immunization coverage for children regardless of where they live.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 23 publications
0
32
2
Order By: Relevance
“…On a related note, not having a clinic close by was a salient barrier to vaccine initiation. Previous research has found that proximity to clinics is related to vaccine compliance for other childhood vaccines (Fu, Cowan, McLaren, Engstrom, & Teach, 2009). Lacking information about the benefits was the final most salient barrier mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…On a related note, not having a clinic close by was a salient barrier to vaccine initiation. Previous research has found that proximity to clinics is related to vaccine compliance for other childhood vaccines (Fu, Cowan, McLaren, Engstrom, & Teach, 2009). Lacking information about the benefits was the final most salient barrier mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…A dichotomous (yes/no) variable was also constructed for whether at least one immunization clinic existed within a 3-mile radius of each neighborhood’s geographic centroid. Several prior studies have suggested the average distance to health care facilities in urban areas is between 2 to 5 miles [25, 29, 33]. This study started with a 3-mile radius but also examined 1-mile and 5-mile radii as a sensitivity analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Fu and colleagues found that low-income, urban children living closer to pediatricians were more likely to be up to date with childhood vaccinations [25]. Other studies have shown that geographic accessibility to health-related resources, including safety-net clinics, food stores, and open space, are not equitable across racial/ethnic groups or socioeconomic status [3035].…”
Section: Introductionmentioning
confidence: 99%
“…A good illustration of these techniques is a study that assessed the relationship between immunization and proximity to pediatric providers using the Washington, DC Immunization Information System. 53 Geospatial techniques could also be used to gather the data necessary to develop highly specific prediction models regarding which individuals are at risk for a VPD during an outbreak, because these predictions not only include the proportion of unimmunized (susceptible) individuals within a population, but also how likely susceptible individuals are to come into contact with one another. …”
Section: Enhancing School Exemption Datamentioning
confidence: 99%